2014
DOI: 10.1016/j.nbd.2013.09.005
|View full text |Cite|
|
Sign up to set email alerts
|

Efficient derivation of cortical glutamatergic neurons from human pluripotent stem cells: A model system to study neurotoxicity in Alzheimer's disease

Abstract: Alzheimer's disease (AD) is among the most prevalent forms of dementia affecting the aging population, and pharmacological therapies to date have not been successful in preventing disease progression. Future therapeutic efforts may benefit from the development of models that enable basic investigation of early disease pathology. In particular, disease-relevant models based on human pluripotent stem cells (hPSCs) may be promising approaches to assess the impact of neurotoxic agents in AD on specific neuronal po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 45 publications
0
75
1
1
Order By: Relevance
“…Furthermore, genetic and epigenetic variability among patients may influence pharmacological responsiveness [45]. Disease modeling using iPS cells for AD has been actively pursued recently and has shown that pharmacological assays can be readily performed using these models [46][47][48][49][50][51][52]. Modeling and screening using glial-neuron coculture and 3-dimensional cultures, both of which better resemble in vivo physiological states, should also be pursued [53,54].…”
Section: Phenotypic Approachesmentioning
confidence: 99%
“…Furthermore, genetic and epigenetic variability among patients may influence pharmacological responsiveness [45]. Disease modeling using iPS cells for AD has been actively pursued recently and has shown that pharmacological assays can be readily performed using these models [46][47][48][49][50][51][52]. Modeling and screening using glial-neuron coculture and 3-dimensional cultures, both of which better resemble in vivo physiological states, should also be pursued [53,54].…”
Section: Phenotypic Approachesmentioning
confidence: 99%
“…The diversity of human brain cell subtypes results in the selective cell death or region/circuit-specific dysfunctions in a variety of neurological diseases [9,65]. However, numerous neuronal subtypes, complicated cellular interactions, and diverse genetic background of the patients pose a difficulty for drug development and disease modeling.…”
Section: Effects Of Aβ(1-42) Oligomers That Induce Disease-specific Nmentioning
confidence: 99%
“…While some disease progressions (e.g., amyloid-β plaques) may take years, in vitro neural models derived from hiPSCs can be used to probe disease on-set and development in a shortened time frame [8]. Another advantage of in vitro models derived from hiPSCs is the ability to generate specific neuronal subtypes, which are known to exhibit differential susceptibility to diseasespecific molecules [9,10]. For example, cortical neurons derived from hiPSCs have been used to screen anti-amyloid β (Aβ) drugs and to evaluate Aβ-induced toxicity [9,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One method to produce human neurons suitable for disease modeling is by differentiating human iPSCs (hiPSCs) or human embryonic stem cells (hESCs) into desired neural lineages, such as cortical pyramidal neurons, striatal interneurons, motor neurons, or dopaminergic neurons [31][32][33][34][35][36][37][38][39][40][41][42]. Importantly, hiPSC-derived neurons are functionally active, and can respond to synaptic stimulation and specific sensory response-evoking ligands [43][44][45][46][47][48][49].…”
Section: The Need For Human Neurologic Disease Modelsmentioning
confidence: 99%